Cutting Red Tape in Lima : How Municipal Simplification Improves Investment Climate - Sislen, David (World Bank, Washington, DC, 2012)
Regulatory simplification has become a part of many countries' efforts to improve the investment climate and the overall economy. Reducing red tape can lift constraints on private sector development and foster economic growth. In Latin America, where decentralization has advanced considerably in recent years, there is emerging consensus as to the need to focus reforms at the municipal level, where barriers tend to be especially high. The experience of Lima, Peru shows how streamlining municipal business registration and licensing procedures can lead to positive economic outcomes.